Facile Synthesis of Zinc Indium Oxide Nanofibers Distributed with Low Content of Silver for Superior Antibacterial Activity. Issue 4 (6th January 2023) - Zheng, Zhibao; Liang, Weizhen; Lin, Renzhi; Hu, Zhe; Wang, Yichao; Lu, Hongsheng; Zhong, Wenwu; Shen, Shijie; Pan, Yin
Abstract : Exploring new antibacterial materials is of great significance for limiting the transmission of germs and protecting human health. Although Ag and oxide nanoparticles have both been extensively used in the field of antibacterial, it is still urgently need to figure out how to combine their characteristics for sterilization. Herein, ZnO/In2 O3 ‐Ag nanofibers are prepared with uniformly dispersed Ag through a facile method of electrospinning and subsequent sintering. The obtained nanofibers are of high purity and have diameters from 90 to 110 nm. The silver is in a zero‐valent state, which is beneficial for sterilization. The quantitative test of bacterial activity shows that the nanofibers are bactericidal for both Staphylococcus aureus and Escherichia coli, with an especially strong inhibitory effect on E. coli . At relatively low concentrations, 98% of E. coli can be killed. Herein, light is shed on exploring more complexes of oxide nanomaterials and Ag for sterilization. Abstract : ZnO/In2 O3 ‐Ag nanofibers with uniformly dispersed Ag are prepared through a facile method of electrospinning and subsequent sintering. The nanofibers are of high purity and have diameters from 90 to 110 nm. It has a remarkable bactericidal effect on Escherichia coli . The 98% of the bacteria can be killed at a relatively low concentration.